El secado de la yuca para la alimentacion animal - Ospina Patiño, Bernardo; Gómez G., Guillermo G.; Best, R. (International Center for Tropical Agriculture, 1983)
The process of cassava drying using a natural, low cost system applicable on the on-farm level is described in detail. This system allows cassava to be stored for long periods to be used in preparing balanced feed rations in substitution of sorghum and other cereals. The process is simple and can be carried out by farmers, thus enabling more efficient land and labor use. The described process includes: weighing, chipping, spreading chips on concrete floors for sun drying, turning the chips over, collection, storage, and commercialization. Aspects on the organization and management of a cassava drying plant are included as well as the costs, forms of financing, and production. (CIAT)